Kinetics and mechanism of BaLaCuS3 oxidation - Azarapin, Nikita O.; Khritokhin, Nikolay A.; Atuchin, Victor V.; Gubin, Alexey A.; Molokeev, Maxim S.; Mukherjee, Shaibal; Andreev, Oleg V. (Crystals)
The oxidation reactions of BaLaCuS3 in the artificial air atmosphere were studied at different heating rates in the temperature range of 50–1200 °C. The oxidation stages were determined by DSC-TG, XRD and IR–vis methods. The kinetic characteristics of the proceeding reactions were obtained with the use of the Kissinger model in a linearized form. Compound BaLaCuS3 was stable in the air up to 280 °C. Upon further heating up to 1200 °C, this complex sulfide underwent three main oxidation stages. The first stage is the formation of BaSO4 and CuLaS2. The second stage is the oxidation of CuLaS2 to La2O2SO4 and copper oxides. The third stage is the destruction of La2O2SO4. The final result of the high-temperature treatment in the artificial air atmosphere was a mixture of barium sulfate, copper (II) oxide and La2CuO4. The mechanism and stages of BaLaCuS3 oxidation and further interactions of the components were discussed.